2014
DOI: 10.1007/s12275-014-3420-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of extended-spectrum and plasmid-mediated AmpC β-lactamases in Enterobacteriaceae isolates from portuguese health care facilities

Abstract: A group of 124 Enterobacteriaceae isolates resistant to third generation cephalosporins, and collected in distinct health care facilities of different Portuguese regions was analysed. The great majority of the isolates were also resistant to fourth generation cephalosporins (83.9%), monobactam (96%), amoxicillin plus clavulanic acid (85.5%), and piperacillin plus tazobactam (66.9%). Overall, 84.7% (105/124) were multidrug resistant. Molecular methods enabled us to identify 86.3% (107/124) extended-spectrum β-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…Moreover, it is worth noting that, the principal source of isolation the ESBL-producing isolates in our study was urine with the proportion 52.38%; our results are in accordance with other recent studies realized on a group of 124 Enterobacteriaceae isolates resistant to third generation cephalosporin, and collected in distinct health care facilities of different Portuguese regions, which have even described a 58.9% clinical strains were isolated from urine (Jones-Dias et al, 2014). However, studies have shown that ESBL producing uropathogens have their reservoir in the digestive tract (Anil Kumar and Babu, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it is worth noting that, the principal source of isolation the ESBL-producing isolates in our study was urine with the proportion 52.38%; our results are in accordance with other recent studies realized on a group of 124 Enterobacteriaceae isolates resistant to third generation cephalosporin, and collected in distinct health care facilities of different Portuguese regions, which have even described a 58.9% clinical strains were isolated from urine (Jones-Dias et al, 2014). However, studies have shown that ESBL producing uropathogens have their reservoir in the digestive tract (Anil Kumar and Babu, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The principal ESBL identified in this study was CTX-M-15, which corresponds to the predominant ESBL found among clinical Enterobacteriaceae in Portugal [ 24 , 39 , 40 ] and worldwide [ 41 ]. This ESBL was actually massively detected among healthy pigs in Portugal [ 42 ], either in E. coli or K. pneumoniae .…”
Section: Discussionmentioning
confidence: 99%
“…Double disk synergy test was used to phenotypically detect the presence of specific groups of β-lactamases in the 333 isolates: amoxicillin (25 μg) and amoxicillin plus clavulanic acid (20 + 10 μg) for the phenotypic detection of penicillinases, cefotaxime (5 μg) and amoxicillin clavulanic acid (20 + 10 μg) for ESBL, cefoxitin (30 μg) and cloxacillin (750 μg) for AmpC β-lactamases, and imipenem (5 μg) and imipenem plus dipicolinic acid (750 μg) for metallo-β-lactamases. Escherichia coli ATCC® 25922™ was also tested as a control of this technique (Jones-Dias et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%